Pemberdayaan kader kesehatan tentang latihan gerak range of motion (ROM) - Andri Yulianto; Reni Tri Subekti; Tiara Tiara (JOURNAL of Public Health Concerns, 2026)
Background: Shoulder joint disorders in the elderly such as frozen shoulder, stiffness, pain, and reduced range of motion can hinder daily activities, diminish independence, and impact quality of life. Limited access to rehabilitation services in rural Thailand necessitates strengthening promotive and preventive services delivered by village health volunteers, who play a strategic role within the community. Purpose: To empower health volunteers to understand, practice, and educate the community on safe range-of-motion (ROM) exercises for the elderly. Method: This international community service activity was conducted over three days in the partner village in Thailand. Twenty-four individuals comprising village health volunteers and community representatives involved in basic community health services participated in the program. The activity aimed to build participant capacity, enabling them to understand, practice, and disseminate education regarding ROM exercises for the elderly. Participant knowledge was assessed using a questionnaire, while skills were evaluated through direct observation during ROM practice simulations. The activity was evaluated based on four key indicators: increased knowledge through health education, improved skills through ROM training, the participants' ability to perform ROM exercises independently, and their ability to educate the community on ROM exercises. Data are presented descriptively using frequencies, percentages, and mean scores. Results: The proportion of participants in the "good" knowledge category increased from 25.0% to 87.5%, and the average knowledge score rose from 60.0 to 86.0. Regarding ROM practice skills, 91.7% fell into the "good/very good" category; 91.7% demonstrated the ability to perform the practice independently or with minimal assistance; and 83.3% achieved a "good/very good" rating for ROM education skills. Conclusion: An international community service program utilizing integrated cadre empowerment proved highly effective in enhancing knowledge and independent skills, as well as improving the cadres' capacity and readiness to provide further education to the community. Empowering cadres through outreach, demonstrations, and hands-on practice proved relevant for strengthening community-based health services. Suggestion: Village health cadres are encouraged to apply their ROM knowledge and skills consistently and to practice independently to ensure movements are precise, safe, and performed with confidence when assisting the elderly. It is also recommended that local partners or BCNs facilitate program sustainability by monitoring cadre activities post-training, thereby supporting the implementation of ROM exercises for the elderly or their families. Keywords: Cadre empowerment; Elderly; Health education; Range of motion; Thai partner village Pendahuluan: Gangguan sendi bahu pada lansia, seperti frozen shoulder, kekakuan, nyeri, dan penurunan rentang gerak, dapat menghambat aktivitas harian, menurunkan kemandirian, serta memengaruhi kualitas hidup. Keterbatasan akses layanan rehabilitasi di wilayah pedesaan Thailand menuntut adanya penguatan layanan promotif-preventif berbasis kader kesehatan desa yang memilki peran strategis di tengah masyarakat. Tujuan: Untuk memberdayakan kader kesehatan agar mampu memahami, mempraktikkan, dan mengedukasi masyarakat mengenai latihan gerak range of motion (ROM) yang aman bagi lansia. Metode: Kegiatan pengabdian masyarakat internasional ini dilaksanakan selama 3 hari di Desa binaan Thailand. Melibatkan 24 peserta yang terdiri atas kader kesehatan desa dan perwakilan masyarakat yang berperan dalam pelayanan kesehatan dasar komunitas untuk menjadi partisipan. Sasaran kegiatan adalah peningkatan kapasitas peserta agar mampu memahami, mempraktikkan, dan menyebarluaskan edukasi latihan ROM kepada lansia. Instrumen pengukuran pengetahuan partisipan menggunakan kuesioner dan untuk penilaian ketrampilan partisipan dengan melakukan observasi langsung terhadap partisipan dalam melaksanakan simulasi praktik ROM. Evaluasi kegiatan dilakukan melalui empat indikator utama: peningkatan pengetahuan melalui penyuluhan kesehatan, peningkatan keterampilan melalui pelatihan ROM, kemampuan peserta melakukan latihan ROM secara mandiri, dan kemampuan peserta melakukan edukasi ROM kepada masyarakat. Data disajikan secara deskriptif dalam bentuk frekuensi, persentase, dan rata-rata skor. Hasil: Menunjukkan secara proporsional partisipan dalam kategori pengetahuan "baik" meningkat dari 25.0% menjadi 87.5%, dan rata-rata skor pengetahuan naik dari 60.0 menjadi 86.0. Terkait keterampilan praktik ROM, 91.7% termasuk dalam kategori "baik/sangat baik"; 91.7% menunjukkan kemampuan praktik secara mandiri atau hampir mandiri; dan 83.3% mencapai peringkat "baik/sangat baik" untuk keterampilan edukasi ROM. Simpulan: Program pengabdian masyarakat internasional melalui pemberdayaan terintegrasi pada kader sangat efektif dalam meningkatkan pengetahuan dan keterampilan mandiri serta meningkatkan kemampuan dan kesiapan kader dalam memberikan edukasi lanjutan kepada masyarakat. Pemberdayaan kader melalui kegiatan penyuluhan, demonstrasi, dan praktik langsung terbukti relevan untuk memperkuat pelayanan kesehatan berbasis komunitas. Saran: Kader kesehatan desa diharapkan menerapkan pengetahuan dan keterampilan ROM secara berkelanjutan dan melakukan pengulangan praktik secara mandiri agar gerakan semakin tepat, aman, dan percaya diri saat mendampingi lansia. Diharapkan juga kepada mitra lokal atau BCN untuk memfasilitasi keberlanjutan program melalui pemantauan kegiatan kader setelah pelatihan sebagai dukungan penerapan latihan ROM kepada lansia atau keluarga.